Boradigermaallyl: (4+3) Cycloaddition‐Initiated Boron Insertion into Benzene. Issue 18 (24th March 2023) - Kern, Ralf H.; Schneider, Meike; Eichele, Klaus; Schubert, Hartmut; Bettinger, Holger F.; Wesemann, Lars
Abstract: The 2π electron 1, 3‐dipole boradigermaallyl, valence‐isoelectronic to an allyl cation, is synthesized from a bis(germylene). It reacts with benzene at room temperature by insertion of a boron atom into the benzene ring. Computational investigation of the mechanism shows the boradigermaallyl reacting with a benzene molecule in a concerted (4+3) or [π4s+π2s] cycloaddition reaction. Thus, the boradigermaallyl acts as a highly reactive dienophile in this cycloaddition reaction with nonactivated benzene as diene unit. This type of reactivity provides a novel platform for ligand assisted borylene insertion chemistry. Abstract : Boradigermaallyl featuring a delocalized π‐bond shows a boron atom insertion into benzene at room temperature. The mechanism starts by a concerted (4+3) reaction between the germanium atoms of the digermaboraallyl and the 1, 4‐positions of a benzene molecule. Thus, boradigermaallyl acts as a highly reactive dienophile in this cycloaddition reaction with nonactivated benzene.